Corruption component of the political process in the post-soviet space - Ю. К. Маслов (Granì, 2019)
Based on the theoretical developments of the corruption phenomenon and its varieties, as well as data from international rating agencies for measuring corruption in the countries of the World, an analysis of the impact of political corruption and its modern manifestations on the political process of the postSoviet countries and Ukraine in particular has been carried out. The study showed the importance of the corruption component in the political processes of the countries of this group, as well as the significant differences between them in the level of the influence of corruption on the content and nature of political events. The author singles out a group of Baltic countries, for which the anti-corruption component is identical to the European standards for the political process implementation, as it is evidenced by the high rates of the Corruption Perception Index. Success in the fight against political corruption, these countries have reached in the process of preparing for accession to the EU, in particular by holding lustration, introducing a mixed form of financing political parties, introducing e-democracy tools, the maturity of civil society, political will of politicians, etc. At the same time Estonia, which has the highest anti-corruption rating, is not without manifestations of political corruption. Its manifestations such as nepotism and favoritism require further action to eliminate their influence on the political process. It was found that the opposite attitude to the corruption component is observed in Asian countries, where political corruption is firmly intertwined with the economic one and does not just influence the political process, but forms its content. It is substantiated that the fight against corruption in such states should begin with the reform of the power system and the formation of a civil society. It was emphasized that Ukraine has its own unique scenario of fighting political corruption, which combines the democratic patterns of European countries, in particular, institutionally follows the path of the Baltic countries, and Asian traditions of exercising power, where types of political corruption are traditional instruments of exercising power in society. It is proved that for further democratization of the political process in Ukraine, it is advisable to strengthen the anti-corruption component by introducing mechanisms to eliminate party corruption, improve the process of financing political parties and their political advertising, electoral corruption, popularize e-democracy tools, prevent manifestations of political nepotism, favoritism, etc.